Investigando a influência das crenças de alunos do Curso de Letras da Universidade Federal do Pará sobre sua prontidão para a aprendizagem autônoma do inglês: um estudo de caso - NASCIMENTO, Cleuma de Almeida Matos (Universidade Federal do Pará, 2011)
This study aims at investigating how the beliefs about English as a foreign language of four undergraduate students of Letras course at UFPA influence, in a positive or negative way, their readiness for autonomous learning. The principles of this research are qualitative with the use of narratives, a questionnaire and interviews for data collecting and further cross validation. By analysing the beliefs and their relation with autonomous learning we concluded that teachers and students can together construct a new understanding of the teaching and learning process, as well as they can better comprehend their roles in it. This awareness is one of the foundations of learner autonomy.